Comparison of efficacy and safety between simultaneous integrated boost intensity-modulated radiotherapy and conventional intensity-modulated radiotherapy in locally advanced non-small-cell lung cancer: a retrospective study - Wang, Daquan (Radiat Oncol, 2019)
BACKGROUND: Consistent results are lacking as regards the comparative effectiveness of simultaneous integrated boost intensity-modulated radiotherapy (SIB-IMRT) versus conventional intensity-modulated radiotherapy in patients with locally advanced non-small-cell lung cancer (LA-NSCLC). Therefore, we conducted a retrospective analysis to demonstrate the role of SIB-IMRT for patients. METHODS: Patients who had histologically confirmed NSCLC, stage III disease and received thoracic IMRT between 2014 and 2016 were retrospectively reviewed. The survival, toxicities and dose to organs at risk (OAR) were compared among patients irradiated with different techniques. The SIB-IMRT plans were designed to deliver 45–59.4Gy (median: 50.4Gy) to PTV while simultaneously delivering 50-70Gy (median: 59.92Gy) to PGTV. As for conventional IMRT plans, a total dose of 50-70Gy (median: 60Gy) was delivered to PTV. RESULTS: 426 patients with stage III NSCLC were eligible for analysis, including 128 with SIB-IMRT and 298 with conventional IMRT. The SIB-IMRT group had more stage IIIB disease (69.5% vs. 53%, P = 0.002), larger planning treatment volumes (median: 504 ml vs. 402 ml, P<0.001), and a larger planning treatment volume/volume of lung ratio (median, 0.18 vs. 0.12, P<0.001). The median OS of the SIB-IMRT and conventional IMRT groups were 34.5 and 31.7 months, with the 2-year rate of 60.4 and 59%, respectively (P = 0.797). No difference in PFS, LRFS or DMFS was observed between the two techniques. Patients treated with SIB-IMRT got similar lung and esophageal toxicities versus those with conventional IMRT. CONCLUSIONS: SIB-IMRT may be an effective and safe option for patients with locally advanced NSCLC, especially for those with large mass or wide lymph node metastasis.